Thermodynamic assessment of the (LiF+UF3) and (NaF+UF3) systems - Beilmann, Markus; Beneš, O.; Konings, R. J. M.; Fanghänel, Thomas (The journal of chemical thermodynamics, 2013)
In this article new thermodynamic descriptions of the (LiF+UF3) and the (NaF+UF3) systems based on new calorimetric data are presented. The experimental investigations were carried out using differential scanning calorimetry (DSC) to obtain phase transition temperatures between (0 and 60)mol% of UF3. On the basis of these measurements a thermodynamic assessment of the (LixU1-x)F3-2x and (NaxU1-x)F3-2x liquid solutions, using the quasi-chemical model was achieved. UF3 undergoes a disproportionation at higher temperatures to UF4 and U metal which had a significant impact on the transition temperatures in the (LiF+UF3) system. For this reason the influence of the presence of up to 15mol% of UF4 in this system was calculated and compared to the experimental results. The final thermodynamic description was corrected for the pure binary system.
Im Titel ist die Zahl 3 tiefgestellt
Gesehen am 20.11.2020
First published: 14 August 2012